Unconscious manifestations in the leader-follower relationship: contributions of psychoanalytic theory to organizational studies - Godoi, Christiane Kleinübing (2017)
This study aimed to understand the unconscious manifestations that transgress the leader-follower relationship in organizations. These dyads were formed by opposing dependent pairs, namely: transference-counter transference; projection-introjection; idealization-identification – Freud’s constructs and all of them unconscious phenomena. The theoretical framework presents the history of the psychoanalytic approach of organizations: a) the analysis of psychoanalytic studies, from the social field to the organizational field (considering that, according to Freud, the unconscious is social. In this section the reader will find a brief tour of the five so-called Sociological Studies of Freud); b) the core of the theoretical framework is already constituted by a psychoanalytic reading of the phenomena of leadership, and finally; c) the theory about the three main unconscious dyads that act in the leader-follower relationship. As a method, psycho-sociology and Lévy's clinical interview were used. The results allow psychoanalytic interpretations by identifying the presence of the dyads, in both leaders and followers discourse. The analysis of the results initially planned in the objectives of this study had to be – for many reasons – altered during the research. One of the reasons is that the relation transference-counter transference dyad found during the study was more complex than expected and that could not be ignored in the analysis. As one of the relations most evidenced, the analysis of the transference-counter transference dyad allows a better understanding of the way in which the identification is generated from the dual relationship between projection and introjection.